2007
DOI: 10.1158/0008-5472.can-06-2593
|View full text |Cite
|
Sign up to set email alerts
|

Human Bone Marrow Activates the Akt Pathway in Metastatic Prostate Cells through Transactivation of the α-Platelet–Derived Growth Factor Receptor

Abstract: The factors regulating the bone tropism of disseminated prostate cancer cells are still vaguely defined. We report that prostate cancer cells that metastasize to the skeleton respond to human bone marrow with a robust stimulation of the phosphatidylinositol 3-kinase/Akt pathway, whereas prostate cells that lack bone-metastatic potential respond negligibly.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 29 publications
3
37
0
Order By: Relevance
“…When PC3-N cells were stably transduced with the cDNA for human PDGFRa, they showed a significant increase in downstream Akt phosphorylation in response to PDGF-AA as compared to their wild-type counterparts ( Figure 3d). We have previously described that human bone marrow aspirates are able to activate Akt in PC3-ML cells by recruiting PDGFRa (Dolloff et al, 2007). When PC3-N(PDGFRa) cells were tested upon similar conditions, we observed a phosphorylation of Akt comparable to that detected in PC3-ML cells (Figure 3e .…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…When PC3-N cells were stably transduced with the cDNA for human PDGFRa, they showed a significant increase in downstream Akt phosphorylation in response to PDGF-AA as compared to their wild-type counterparts ( Figure 3d). We have previously described that human bone marrow aspirates are able to activate Akt in PC3-ML cells by recruiting PDGFRa (Dolloff et al, 2007). When PC3-N(PDGFRa) cells were tested upon similar conditions, we observed a phosphorylation of Akt comparable to that detected in PC3-ML cells (Figure 3e .…”
Section: Resultssupporting
confidence: 66%
“…As osteoclast involvement appears to be a delayed event in metastatic progression, single cells and small foci would initially have to rely on the trophic support exerted by factors immediately available in the bone marrow stroma, through the stimulation of compatible cellular receptors. We have previously reported that PC3-ML cells express high levels of PDGFRa, a tyrosine-kinase receptor responsible for a strong in vitro activation of the PI3K/Akt survival pathway in response to human bone marrow (Dolloff et al, 2007). The PC3-N prostate cancer cellsa non-invasive counterpart of PC3-ML cells (Wang and Stearns, 1991)-express low levels of PDGFRa, whereas brain metastasis-derived DU-145 prostate cells lack this receptor (Dolloff et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Olaratumab blocks ligand binding and receptor dimerization by specifically binding to PDGFRa and as such is able to suppress potential kinase domain-independent signaling (37). Furthermore, olaratumab-bound PDGFRa is internalized and degraded, which attenuates downstream pathway activation and likely further contributes to drug activity (8,37).…”
Section: Discussionmentioning
confidence: 99%
“…92 PDGF receptors constitute promising targets for anticancer therapies as they are involved in the proliferation and survival of different tumors as well as in the regulation of the as immunostimulatory agents by taking T cells in the close proximity of tumor cells. 28,109,110 Another interesting approach that is being tested in phase I-II trials is known as pre-targeted radioimmunotherapy and is exemplified by TF2, a bispecific mAb that simultaneously targets the tumor-associated carcinoembryonic antigen (CEA) and a heterologous hapten peptide (IMP-288).…”
Section: Monoclonal Antibodies Under Early (Phase I-ii) Clinical Evalmentioning
confidence: 99%